Persepsi polis tentang kehidupan kerja yang berkualiti (KKB) : satu tinjauan di tiga balai polis terpilih di kawasan Kuching / Samarahan - Crispin, Ak Francis (Universiti Malaysia Sarawak (UNIMAS), 2001)
This research was carried out to investigate the indicators that influence polices perception towards the Quality of Work Life (QWL) in police organisation. A total of 40 respondents were chosen by using a simple random sampling methods and questionnaires. This study identifies the overall QWL level and INdividual level for the different indicators. The independent variables in this research were gender. position. age. year ofservice. marital status and amount ofdependant. The dependent variables were the eIg/It KKB indicators. which include reward. safety. and social interaction within organisation. autonomy. feetlbaclc.job design, job involvement and quality offamily life. This study also looks into the priorities of the different indicators and the differences of QWL level based on the demographic characteristics of respondents. The finding from the research showed that the level ofQWL in police organisation was at a lower level (Mean = 2.30). Thefindings showed, respondents were most satisfied with thejob involvement at the work place (Mean = 2.65) while respondents were least satisfied wilh the reward and feedback gtWIII (Mean = 2.20). When respondents were asked for their priorities in determining their QWL. the result showed the reward indicator was given the first priority. In addition, the result however did not show any differences on the level of QWL based on their demographic characteristics. which include gender. position. age. and year ofservice. marital status and amount ofdependant. The findings ofthis study also showed that there was no Significant relationship between age and year of service towards QWL.